2008
DOI: 10.1111/j.1538-7836.2008.03039.x
|View full text |Cite
|
Sign up to set email alerts
|

Rapid resensitization of purinergic receptor function in human platelets

Abstract: Summary. Background: Adenosine diphosphate (ADP) is a critical regulator of platelet activation, mediating its actions through two G protein-coupled receptors (GPCRs), the P2Y 1 and P2Y 12 purinergic receptors. Recently, we demonstrated that both receptors desensitize and internalize in human platelets by differential kinase-dependent mechanisms. Objectives: To demonstrate whether responses to P2Y 1 and P2Y 12 purinergic receptors resensitize in human platelets and determine the role of receptor traffic in thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
69
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(74 citation statements)
references
References 36 publications
5
69
0
Order By: Relevance
“…3 Recent work from our laboratory has shown that P2Y 12 receptor (P2Y 12 R) responsiveness is rapidly and reversibly modulated in human platelets. 4 On prolonged exposure to agonist, the responsiveness of P2Y 12 R, in human platelets, decreases because of receptor desensitization 5 and subsequent internalization. 6 In cell lines P2Y 12 Rs are regulated in a G protein-receptor coupled kinase (GRK)-dependent manner, 5 leading to their rapid recruitment to clathrin-coated pits (CCPs) in an arrestin-dependent manner.…”
Section: Introductionmentioning
confidence: 99%
“…3 Recent work from our laboratory has shown that P2Y 12 receptor (P2Y 12 R) responsiveness is rapidly and reversibly modulated in human platelets. 4 On prolonged exposure to agonist, the responsiveness of P2Y 12 R, in human platelets, decreases because of receptor desensitization 5 and subsequent internalization. 6 In cell lines P2Y 12 Rs are regulated in a G protein-receptor coupled kinase (GRK)-dependent manner, 5 leading to their rapid recruitment to clathrin-coated pits (CCPs) in an arrestin-dependent manner.…”
Section: Introductionmentioning
confidence: 99%
“…In order to minimize inappropriate platelet recruitment and activation at the site of a growing thrombus, platelet ADP responsiveness is tightly regulated in human platelets (8)(9)(10)(11)(12). P2Y 12 receptor responsiveness rapidly desensitizes in human platelets (13).…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
“…Previous studies in cell lines have identified that G protein-coupled receptor kinase (GRK)2-and GRK6-dependent phosphorylation of the P2Y 12 receptor is required for arrestin association and desensitization (9). Following removal of ADP there is a rapid resensitization of P2Y 12 receptor responsiveness in human platelets (11). In order to resensitize, the P2Y 12 receptor internalizes following agonist addition and then recycles back to the cell membrane following removal of ADP (11).…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
See 2 more Smart Citations